Unveiling the Dynamics of African Post-Colonial Administration: A Holistic Analysis of Devil on the Cross - Souleymane Diallo (Borong Newinera Publisher, 2023)
Through the frame frequency of the imported state and the westernization of the African political order, the social construction of the African bureaucracy appears as a structural device of abstraction, exploitation, and brutality. Then, through the frame of reference with the importation of conceptual juridical coordination and perceptual representative consensus, the African public administration enhances a frameshift transformation and a succession of causality. Therefore, in combinatorial and transactional analysis, the framework of Devil On The Cross progresses in a method of empirical processing decomposition. Within this respect, the elemental and pure imaginary of the African administration proceeds as a functional derivative governmentality and a colonial functional inception power. Subsequently, with its interaction design, processing system, and volume technique, the realm of Devil on The Cross inserts a paradigmatic analysis and a value engineering within which this African administration happens as an characteristic structural formula and an inefficient relational frame theory. Moreover, within the space-time continuum, the configuration management and the linear configuration programming of the African management apparatus, Devil On The Cross becomes a holomorphic function and an analytic continuation that reveal the anachronism nature and the asynchronous system of the African post-colonial administration.